Population Pressure and Livelihood Dynamics: Panel Evidence from Bangladesh - Rashid, Shahidur; Tefera, Nigussie; Lemma, Solomon; Yunus, Mohammad (International Food Policy Research Institute, 2014)
Since the publication of the World Development Report 2008, two related strands of research have emerged-one on the validity of smallholder-led development strategy and the other on agricultural intensification under population pressure. The former casts doubt about the role of agriculture in economic development in smallholders dominated countries and the later provides evidence that are contrary to earlier findings on induced innovation theory. Using a unique panel dataset, we examine whether these arguments are valid for Bangladesh--a densely populated country that has experienced significant growth in recent decades. The results suggest that (1) agriculture as a source of income declined significantly over the past two decades; (2) the operated farm size stopped declining in the late 1980s; and (3) that population density relates positively with a host of agricultural intensifications indicators with no evidence of threshold.